Smart systems to mitigate failure of strategic alliances - Cunha, S.; Lopes da Costa, R.; Gonçalves, R.; Pereira, L.; Dias, Á. (International Journal of Productivity and Quality Management, 2023)
Despite the strategic importance of alliances and the numerous benefits that this corporate strategy brings to companies, success rates are still very low, with several causes of failure presented in the literature. On the other hand, the implementation of smart systems has proved to be very promising when applied to the different tools of business management. In order to find solutions to this problem, the main objective of this investigation was to study the impact that the use of smart systems has on the operational optimization of the company and in mitigating the causes of failure of strategic alliances in Portugal. This research used a qualitative approach, through the content analysis of 17 interviews with managers and professionals in the area. The study concludes that the implementation of smart systems has the potential to mitigate 7 of the 10 main causes of failure of strategic alliances. Also, concerning the future of the implementation of smart systems, it was concluded that the traditional models of strategic alliances are being questioned regarding their effectiveness and adequacy in dealing with the new market challenges brought about by technological development and should therefore be rethought and adapted to a more collaborative and integrated model.